Sustitución del Carbonato de Calcio (caco3) por Harina de Cáscaras de Huevo en un Balanceado para Cuyes en la etapa de Recría. - Vásquez Chicaiza, Diana Isabel (2019)
In the present research project, the replacement of calcium carbonate (CaCO3) by egg shells meal was carried out, in concentrate food for guinea pigs in the breeding stage, through drying temperatures were evaluated at 60 ° C, 80 ° C and 100 ° C for 1 and 2 hours in obtaining the eggshell flour, optimizing the drying process at 80 ° C for one hour. To determine the% calcium, the flour, its physicochemical characteristics (protein, fiber, moisture, ash) and microbiological analysis (aerobic bacteria count, Escherichia Coli and salmonella) were sent to the OSP laboratories of the Central University of Ecuador, Faculty of Chemical Sciences. Additionally, the FORTYCUY balanced diet was carried out, incorporating 1% of eggshell flour, a percentage used for guinea pigs in the breeding stage, fed for 4 weeks, evaluating productive parameters (weight, consumption and mortality). The weight of the 20 animals were recorded weekly, consumption was taken periodically and there was no mortality rate. Similarly, the laboratory was sent to analyze the physicochemical and microbiological characteristics of the FORTYCUY or experimental balancing, as well as the control balancing. Subsequently, the best weight of the animal to be slaughtered and analyze the nutritional characteristics (protein, moisture, fat, carbohydrate ashes, cholesterol, total sugars, fat and calcium) of the meat was taken through a statistical analysis with the t-Student test, comparing it with the values obtained from guinea pigs fed with the concentrate food control. In addition to this, the weight and performance of the carcass was determined. The preparation of balancing is carried out in the premises of the company of Mr. ADAN VENITES and the execution of the raising of guinea pigs in Tiobamba neighborhood, located in Latacunga city, Cotopaxi province.Finally, it was determined that the flour has 3.76% protein, 1.91% crude fiber and 6.42% calcium, benefits offered as raw material against calcium carbonate that is only a calcium source in the diet. Therefore, there was a significant weight gain at 4 weeks of experimentation, since the observations began with weights of 350-370g and its final weight is 700-7001g compared to the witness with final weights of 675-690g. Regarding the nutritional properties in guinea pig meat, it can be established that they are excellent for 17.31% protein, 7.53% fat and 17.81 mg / 100g cholesterol compared to the control, present 15.78% protein, 9.86% fat and 19, 29 mg / 100g cholesterol.